THEORETICAL FOUNDATIONS OF THE CRIME OF PREPARING, STORING, DISTRIBUTING OR DISPLAYING MATERIALS THAT THREATEN PUBLIC SAFETY AND ORDER - Sh. Muhammadjonov (Bright Mind Publishing, 2025)
Liability is established, and these rules serve to protect society from various forms of aggression and ensure the stability of the country. However, a number of problems are observed in the practice of applying these legal norms.